Laparoscopic liver resection in Caroli disease: a single-centre case series - Bellingrath, J; Schoening, W; Wabitsch, S; Brenzing, C; Arnold, A; Fehrenbach, U; Schmelzle, M; Pratschke, J (Medknow Publications, 2020)
Background: Liver resection is the treatment of choice for patients with localised Caroli disease. While liver resection was traditionally performed as open procedure, this case series aims to evaluate the safety and efficacy of minimally invasive, laparoscopic liver surgery in these patients. Methods: A systematic review of electronic case files of patients seen between April 2015 and December 2017 at the Department of Surgery, Charité University Hospital Berlin, was conducted. Patients with Caroli disease in whom laparoscopic liver resection had been performed were identified and analysed in this single-centre case series. Results: Seven patients who underwent laparoscopic liver surgery for Caroli syndrome were identified and presented with a median age of 49 (range = 44–66) years, of which four (57%) were female. Preoperatively, six patients were classified as the American Society of Anaesthesiologists (ASA) 2 and one patient as ASA 3. Two operations were performed as single-incision laparoscopic surgery, whereas the others were done as multi-incision laparoscopic surgery. One patient required a conversion to an open procedure. The length of operation varied between patients, ranging from 128 to 758 min (median = 355). The length of stay in the intensive care unit ranged from 0 to 2 days. Two patients presented with post-operative complications (Clavien–Dindo Grade ≥3a), whereas no patient died. In histopathological analysis, all patients demonstrated characteristic findings of Caroli disease and no cholangiocarcinoma was found. Conclusion: These results indicate that minimally invasive, laparoscopic liver surgery is a safe and efficacious treatment option for patients with Caroli disease who require liver resection.